Modification of Wooden Ball Bullets to Improve the Skillful Motion of Bullet Repellent Games Against Elementary School Students - Thesya Alda Nia; Ali Munir; Bernadeta Suhartini (Edumaspul: Jurnal Pendidikan, 2022)
The modification of wooden ball bullets is a model invention with a combination of woodball sports games with bullet repulsion, this is in line with the conditions both in terms of anthropometry and physical conditions in elementary school students which is certainly less effective when using iron balls, because the learning system in elementary school students is only limited to introducing the game. The purpose of this study is that the modification of the wooden ball bullet model can be implemented for students, especially elementary schools, so that students will feel more happy and happy because the learning is very creative and relatively not monotonous and can minimize the allocation of time and the lack of existing infrastructure. In this study, the researchers used the Class Action Research method with class V student sample data consisting of 22 students. The instruments in this study used observation data collection techniques and bullet repellent skilled motion tests. From the study, it was found that there was an increase in pre-cycle to cycle I with learning completion of (54.53%) and continued in cycle II with learning completion results of (86.38%). Of course, it can be concluded that using a modified model of wooden ball bullets is very useful for the community, especially educators, in an effort to improve the movement of game skills in athletics in the bullet repulsion number.